Social control and information democratization: a process under construction (Revista Latino-Americana de Enfermagem, 2003)
This work aims at a critical reflection on social control as a legal-institutional achievement and its legitimacy conditions, pointing out strategies for information democratization in the local health system. The text was developed according to three thematic units: the first discusses social participation as a legal-institutional achievement; the second analyzes the essential conditions for legitimacy and the third presents information as a fundamental element for management and social control as an unfinished process that is still under construction.